Association between Iron Supplementation, Dietary Iron Intake and Risk of Moderate Preterm Birth: A Birth Cohort Study in China - Yawen Shao; Baohong Mao; Jie Qiu; Yan Bai; Ru Lin; Xiaochun He; Xiaojuan Lin; Ling Lv; Zhongfeng Tang; Min Zhou; Xiaoying Xu; Bin Yi; et al. (Tehran University of Medical Sciences, 2021)
Abstract Background: To evaluate the independent and collective effects of maternal iron supplementation and dietary iron intake upon the risk of moderate preterm birth and its subtypes. Methods: In this birth cohort study, 1019 pregnant women with moderate preterm birth and 9160 women with term birth were recruited at Gansu Provincial Maternity and Child Care Hospital from 2010-2012 in China. Unconditional logistic regression models were utilized to evaluate the association between maternal iron supplementation, dietary iron intake, and the risk of moderate preterm birth and its subtypes. Results: Compared with non-users, iron supplement users exerted a protective effect upon the overall (OR=0.54, 95%CI=0.40-0.72) and spontaneous moderate preterm birth (OR=0.39, 95%CI=0.33-0.83). Compared with the 25th quartiles of dietary iron intake, either before or during pregnancy, it exerted a signiﬁcantly protective effect upon those who had the highest quartiles of dietary iron intake (OR=0.87, 95%CI=0.82-0.95 for the highest quartiles of dietary iron intake before pregnancy OR=0.85, 95%CI=0.79-0.91). Positive association was observed between the additive scale and multiplicative scale for preterm birth, spontaneous preterm rather than medically indicated preterm. Conclusion: Iron supplements (60 mg/day) and high-iron intake (>25.86 mg/day before pregnancy, >30.46 mg/day during pregnancy) reduced the risk of moderate preterm birth. Positive correlation is found between the additive scale and multiplicative scale for preterm birth, spontaneous preterm birth.